Young Mandela - Smith, David James (Blackstone, 2010)
Nelson Mandela is well-known throughout the world as a heroic leader who symbolizes freedom and moral authority. He is fixed in the public mind as the world's elder statesman--the gray-haired man with a kindly smile who spent 27 years in prison before becoming the first black president in South Africa.
Unabridged
Keywords: Mandela, Nelson, 1918-